SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PENERIMA BEASISWA MENGGUNAKAN METODE ELECTRE - Betaria Sonata Sianturi; Volvo Sihombing; Ibnu Rasyid Munthe (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
This study aims to address the problem of determining whether or not students are eligible to receive scholarships at SMP Pembangunan Bagan Batu. Determination of scholarship recipients is done by building a computer-based decision support system that helps make it easier to determine students who are entitled to get the scholarship. Decision support system built using the Electre method. The criteria used in the DSS Electre Method consist of the Average Student Report Card Score, Total Parental Income, Total Dependents of Parents, Total Achievements of the student with a weight of 3,3,2,2 for each criterion. The final result of the DSS Electre method is a recommendation through favorable matrix data which is determined based on the highest number of 1s. The results of this research case study, alternatives with a value of at least 1 can be eliminated. The biggest score was obtained by Alternative Siswa_01 with the highest score of 1.